Research of the g factors, optical band positions and local structure for the tetragonal octahedral (CrO6)7− clusters in glasses. (17th October 2016) - Mei, Yang; Zheng, Wen-Chen; Zhang, Xin-Xin
ABSTRACT: The electron paramagnetic resonance g factors g //, g ⊥ and also the optical band positions of the tetragonal (CrO6 ) 7− octahedral clusters in glasses are calculated from the high-order perturbation formulas (in which the needed crystal-field (CF) energy levels correspond to the optical band positions). The formulas are founded on the two-mechanism model which takes account of both the contribution to g factors from the widely used CF mechanism and that from the frequently neglected charge-transfer (CT) mechanism. The calculated results are in rational agreement with the experimental values, suggesting that the contribution to g factors from CT mechanism should be considered. The local structure of (CrO6 ) 7− clusters in glasses is also acquired from the calculation. The results are discussed. Abstract :